Estimates of the Regression Coefficient Based on Kendall's Tau - Sen, Pranab Kumar (Journal of the American Statistical Association, 1968)
Abstract The least squares estimator of a regression coefficient β is vulnerable to gross errors and the associated confidence interval is, in addition, sensitive to non-normality of the parent distribution. In this paper, a simple and robust (point as well as interval) estimator of β based on Kendall's [6] rank correlation tau is studied. The point estimator is the median of the set of slopes (Yj - Yi )/(tj-ti ) joining pairs of points with ti ≠ ti , and is unbiased. The confidence interval is also determined by two order statistics of this set of slopes. Various properties of these estimators are studied and compared with those of the least squares and some other nonparametric estimators.
MAG ID: 2018764772

At Risk: Natural Hazards, People's Vulnerability and Disasters - Wisner, Benjamin Goodwin; Blaikie, Piers; Cannon, Terry; Davis, Ian J. (1994)
Many disasters are a complex mix of natural hazards and human action. At Risk argues that the social, political and economic environment is as much a cause of disasters as the natural environment. Published within the International Decade of Natural Hazard Reduction, this book suggests ways in which both the social and natural sciences can be analytically combined through a 'disaster pressure and release' model. Arguing that the concept of vulnerability is central to an understanding of disasters and their prevention or mitigation, the authors explore the extent and ways in which people gain access to resources. Individual chapters apply analytical concepts to famines and drought, biological hazards, floods, coastal storms, and earthquakes, volcanos and landslides - the hazards that become disasters'. Finally, the book draws practical and policy conclusions to promote a safer environment and reduce vulnerability.
MAG ID: 2058329721